Association between midlife dementia risk factors and longitudinal brain atrophy: the PREVENT-Dementia study. Issue 2 (5th December 2019) - O'Brien, John T; Firbank, Michael J; Ritchie, Karen; Wells, Katie; Williams, Guy B; Ritchie, Craig W; Su, Li
Abstract : Background: Increased rates of brain atrophy on serial MRI are frequently used as a surrogate marker of disease progression in Alzheimer's disease and other dementias. However, the extent to which they are associated with future risk of dementia in asymptomatic subjects is not clear. In this study, we investigated the relationship between the Cardiovascular Risk Factors, Aging, and Dementia (CAIDE) risk score and longitudinal atrophy in middle-aged subjects. Materials and methods: A sample of 167 subjects (aged 40–59 at baseline) from the PREVENT-Dementia programme underwent MRI scans on two separate occasions (mean interval 735 days; SD 44 days). We measured longitudinal rates of brain atrophy using the FSL Siena toolbox. Results: Annual percentage rates of brain volume and ventricular volume change were greater in those with a high (>6) vs low CAIDE score—absolute brain volume percentage loss 0.17% (CI 0.07 to 0.27) and absolute ventricular enlargement 1.78% (CI 1.14 to 2.92) higher in the at risk group. Atrophy rates did not differ between subjects with and without a parental history of dementia, but were significantly correlated with age. Using linear regression, with covariates of age, sex and education, CAIDE score >6 was the only significant predictor of whole brain atrophy rates (p=0.025) while age (p=0.009), sex (p=0.002) and CAIDE>6 (p=0.017) all predicted ventricular expansion rate. Conclusion: Our results show that progressive brain atrophy is associated with increased risk of future dementia in asymptomatic middle-aged subjects, two decades before dementia onset.